Los primeros pasos de la protección social a los ciegos en España: función y alcance de las instituciones socioeducativas públicas antes de la creación de la O.N.C.E. - Burgos Bordonau, Esther (Cuadernos de Trabajo Social, 2005)
The article shows the beginning of the social public assistance to the blind people in Spain and the later repercussion that this assistance had within the collective in the social aspect as much as in the educative. The steps taken by different institutions to receive blind people and the way in which their instruction was guided is also presented. It is mainly an statistical study that describes the reach of the social educational attention to blind people collective since the appearance of the first schools up to the creation of the National Organization for the blind people in Spain in December 1938 (ONCE).
Keywords: Social assistance; Disability; Beneficence; Instruction; Blindness; ONCE